Ultrasonographic assessment of optic nerve: does it help in lupus-induced optic neuropathy? - Amira Elsonbaty; Abdallah El-Sayed Allam; Doaa M Mahmoud; Sara Alattar; Ahmed Hosny Shaaban (Lupus Science and Medicine)
Objective Evaluating the potential role of neuromuscular ultrasonography (NMUS) in assessing optic nerve affection in patients with systemic lupus erythematosus (SLE), compared with healthy controls and other conventional strategies in diagnosing optic neuropathy.Methods We conducted an observational cross-sectional study comparing patients with SLE and a healthy group. We measured the optic nerve diameter (OND) and optic nerve sheath diameter (ONSD) and calculated the OND/ONSD ratio and side-to-side difference. An ophthalmologist examined all lupus patients and visual evoked potential (VEP) was performed to help evaluate the rule of NMUS in lupus-induced optic neuropathy.Results In this study, we include 140 subjects, 65 lupus patients and 75 controls. Significant enlargement was present among lupus patients OND and ONSD (p= 0.017, 0.004, respectively) in comparison to controls; ultrasonographic evaluation had a high specificity when compared to ophthalmological evaluation and VEP reaching 89.6% and 88.1%, respectively, but with very low sensitivity.Conclusion Ultrasonographic evaluation of the optic nerve may add significant value to the diagnosis of optic neuropathy in patients with SLE and should be considered a complementary tool to other conventional methods.